Saysay himig a sourcebook on Philippine music history, 1880-1941 - Tan, Arwin Q. (Diliman, Quezon City The University of the Philippines Press, 2018)
The chapters are organized around six general themes. These include (1) transmission of music, (2) musical heritage, (3) politics and music, (4) music economy, (5) popular culture, and (6) music communities. Individual topics include but are not limited to audience reception of and writing about music in Manila in various decades; overviews of particular genres or styles— including folk music traditions, rondalla, zarzuela (sarsuwela), bodabil, and opera—in the Philippines; music pedagogy in the Philippines; systems for printing, publishing, selling, and copyrighting music in Manila; and the intersections of US imperialism with music education and performance--Project Muse, Asian Music Volume 53, Number 2, Summer/Fall 2022, pp. 140 (Review)
PART 1: TRANSMISSION OF MUSIC: Chapter 1: Early Writings on Philippine Music, 1880s-1930s / Jose S. Buenconsejo -- Chapter 2: Proposals for a Conservatory of Music, 1870s-1890s / Bayani Santos Jr. -- Chapter 3: “The Magical Means of Great Souls”: Music in Women’s Education in the Nineteenth Century / Marya Svetlana T. Camach0 -- Chapter 4: The First Tagalog Music Theory Book / Arwin Q. Tan -- Chapter 5: The Lineage of Classical Guitar Pedagogy at the UP College of Music / Teresa Canon Garcia -- Chapter 6: Colonized by Rote: Music Education at the Outset of the US Colonial Era in the Philippines / Christi-Anne Castro -- Chapter 7: The Thomasites in Philippine Colonial Education / Raul Casantusan Navarro -- Chapter 8: 1916: The UP Conservatory of Music as a Dream Fulfilled / Bayani Santos Jr. -- Chapter 9: The Confederated Music Schools of Manila in the Early Twentieth Century / Arwin Q. Tan -- Chapter 10: Francisco S. Santiago, 1889-1947: The First Filipino Director of the UP Conservatory of Music / Mauricia D. Borromeo -- Chapter 11: The Academy of Music of Manila, 1931-1941: A Central European-Molded Conservatory / Arwin Q. Tan -- PART 2: MUSIC HERITAGE -- Chapter 12: Roman Catholic Liturgical Music in the Intracolonial Period in the Philippines, 1880-1940 / David J. Kendall -- Chapter 13: The Appropriated Villancio Filipino in the Rituals of Philippine Christmas / Maria Alexandria Inigo Chua -- Chapter 14: Serenata / Jocelyn Timbol-Guadalupe -- Chapter 15: Folk Music Traditions / Edna Aurora C. Culig -- Chapter 16: Diego C. Perez and His Recuerdos de Filipinas y sus Cantares: Gran Potpurri Para Piano, 1886 / Jose S. Buenconsejo -- Chapter 17: Clipping Together Steps and Dancing Them Out: With Francisca Reyes Aquino and After / Basilio Esteban S. Villaruz -- Chapter 18: The Philippine Rondalla, 1880-1940 / Edna Aurora C. Culig -- Chapter 19: Filipino Composers during the American Colonial Period, 1898-1941 / Verna de la Pena -- Chapter 20: Modern Filipino Music before 1950 / Ramon P. Santos (National Artist for Music) -- PART 3: POLITICS AND MUSIC -- Chapter 21: Music, Politics and the Buenaventuras / Resil B. Mojares -- Chapter 22: Music of the Philippine Revolution / Raul Casantusan Navarro -- Chapter 23: Nakpil’s Musical Tribute to the Revolutionary Heroes / Mahler dela Paz Villanueva -- Chapter 24: The Philippine National Anthem / Raul Casantusan Navarro -- Chapter 25: Hearing with an Imperial Ear: Racializing the Philippine Constabulary Band and Black American Conductor Lt. Col. Walter H. Loving / Mary Talusan -- Chapter 26: Articulating Resistance at the Margins of Power: Music of the Iglesia Filipina Independiente / Arwin Q. Tan -- Chapter 27: Minda Mora: Music and Identity in the Early Tagalog Zarzuela / Isidora Miranda -- Chapter 28: The Struggle for Freedom as a Sacred Cause: The Songs of Radical Social Movements, 1930-1941 / Teresita Gimenez Maceda -- PART 4: MUSIC ECONOMY -- Chapter 29: Music Printing and Publishing in Urban Colonial Manila, 1858-1942 / Maria Alexanda Inigo Chua -- Chapter 30: Writing “Filipino”: The Critical Pen on Music in Manila’s Newspapers, 1860-1940 / Ma. Patricia Brillantes Silvestre -- Chapter 31: Keyboards in Nineteenth-Century Philippines / Jose S. Buenconsejo -- Chapter 32: Parish Music History and Economic Administration: Three Case Studies in the Central Visayas / David J. Kendall -- Chapter 33: Selling the Music: Music Stores and Distribution Companies in Colonial Manila, 1873-1942 / Maria Elxandra Inigo Chua -- Chapter 34: Echoing Musical Modernities: Filipino Migrant Musicians from the Nineteenth Century to the Present / meLe yamomo -- Chapter 35: On the Estella-Santiago Dispute: Sublation and Crisis I Intellectual Property Rights in t 1930s Philippines / Jonas Baes -- PART 5: POPULAR CULTURE
Chapter 36: The Manila Tertulia in the Spanish and American Periods: Form Private to Public Sphere / Ma. Patricia Brillantes Silvestre -- Chapter 37: A Very Brief History of the Zarzuela in the Philippines / Isidora Miranda -- Chapter 38: Opera in the Philippines, 1860s-1940s / Raul Casantusan Navarro -- Chapter 39: On the Travelling European Virtuosos / Crisancti L. Macazo -- Chapter 40: The Soundscapes of the Manila Carnival / Raul Casantusan Navarro -- Chapter 41: Bodabil and its Masters / Cristina Maria P. Cayabyab -- Chapter 42: The Rise of the Naughties: Humor in Katy de la Cruz’s “Bodabil” Songs / Maria Rhodora G. Ancheta -- Chapter 43: Tapping Thoughts on Black and Brown Dances in the Americas / Basilio Esteban S. Villaruz -- Chapter 44: Claiming Space for Filipino Music in Colonial Broadcasting: The Contribution of Radio to Filipino Music in the American Period / Elizabeth L. Enriquez -- Chapter 45: Music and Early Cinema in the Philippines: Evolution of the Filipino Musical Film / Nick Deocampo -- PART 6: MUSIC COMMUNITIES -- Chapter 46: Social networking in Musicians’ Unions and Musical Associations / Arwin Q. Tan -- Chapter 47: Music Patronage in Colonial Manila / Raul Casantusan Navarro -- Chapter 48: The Beginnings and Development of the Orchestra in the Philippines / Edna Marcil M. Martinez -- Chapter 49: The Filipino Bandmasters of Nineteenth-Century Spanish Regimental Bands / Arwin Q. Tan -- Chapter 50: The UP ROTC Symphonic Band / Leonardo G. Quinitio.
Includes bibliographical references and index.
Keywords: Music -- Philippines -- History; Performing arts -- Philippines -- History